TRACES OF HIGH SEISMIC ACTIVITY IN THE UPPERMOST SEDIMENTS OF LAKE BAIKAL, SIBERIA - E. G. Vologina; M. Sturm; Ya. B. Radziminovich (Геодинамика и тектонофизика)
Sedimentation in Lake Baikal is significantly affected by continuous seismic activity in the Baikal Rift Zone. Our study shows that historical earthquakes, as well as recent seismic events, considerably influenced sedimentation in this deep tectonic basin. Here we present some of the results of extensive international research activities during the period of 1996–2019. To identify traces of seismic events in the uppermost sediments (<1.5 m), short cores were recovered from many coring stations throughout the entire lake. Based on lithological descriptions, measurements of magnetic susceptibility, and concentration of inorganic and organic components, we identified earthquake indicators in the sediment cores. Impacts of historical earthquakes were traced within South Baikal (near the Sharyzhalgai Station and the Station 106-km of the Circum-Baikal railway, hereafter CBR) and Proval Bay (near the Selenga River delta).